Adolescents and body image : the effect of social media usage, physical activity, and gender - Ingibjörg Bergmann 1995- (2020)
In recent years research has shown that adolescents' body image has deteriorated and the reasons for it are thought to be various. The main purpose of this study is to look more closely at adolescents' body image and the possible effects of social media usage and physical activity on it. The Youth of Iceland 2018 questionnaire from the Icelandic Centre for Social Research and Analysis (ICRSA) was used to conduct the present study. Participants were students in 8th-10th grade in elementary school and their ages ranged from 12-17 years (M = 14.96). A random sample of 2140 participants was used in the study, 1037 females, 1085 males, and 18 participants who did not specify their gender. The results showed that there was a significant difference in body image between the genders and females had worse body image than males. They also revealed that more time spent on social media is associated with worse body image, although there does not appear to be a significant difference between the genders. They also revealed that the more time adolescents spent in physical activity, the more positive body image they had. However, there was not a significant difference between the genders. Keywords: Body image, Body image concerns, Adolescents, Gender differences, Social media usage, physical activity Rannsóknir síðustu ára hafa sýnt að líkamsímynd unglinga hefur farið versnandi og ástæður fyrir því taldar vera mismunandi. Megin tilgangur þessarar rannsóknar er að skoða líkamsímynd unglinga nánar og möguleg áhrif samfélagsmiðlanotkunar og líkamlegrar hreyfingar á hana. Notaður var spurningarlistinn Ungt fólk 2018 frá Rannsóknum og greiningu við gerð eftirfarandi rannsóknar. Þátttakendur rannsóknarinnar voru nemendur í 8- 10 bekk í grunnskóla á aldrinum 12-17 ára (M = 14.96). Handahófskennt úrtak af 2140 þátttakendum var nýtt við gerð rannsókninar, 1037 stelpur, 1085 strákar og 18 sem gáfu ekki upp kyn. Niðurstöður sýndu að það er marktækur munur á líkamsímynd kynjanna og voru stelpur með verri líkamsímynd en strákar. Þær ...